2021
DOI: 10.1177/1759720x211037530
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of treatment options for subacromial shoulder conditions: a systematic review and network meta-analysis

Abstract: Background: There are currently many treatment options for patients with subacromial shoulder conditions (SSCs). Clinical decision-making regarding the best treatment option is often difficult. This study aims to evaluate the comparative effectiveness of treatment options for relieving pain and improving function in patients with SSCs. Methods: Eight databases [including MEDLINE, Embase, CINAHL, AMED, PEDro, Cochrane Database of Systematic Reviews and World Health Organization (WHO) International Clinical Tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Since there is no evaluation tool for the quality assessment on information specif-ically for SAIS, the authors created a novel scoring system (referred to as the subacromial impingement syndrome score, SAISS) based on a literature review and expert opinion [22][23][24][25][26][27]. Comparable approaches were used to create scoring systems in previous studies [11,28,29].…”
Section: Evaluation Of Educational Qualitymentioning
confidence: 99%
“…Since there is no evaluation tool for the quality assessment on information specif-ically for SAIS, the authors created a novel scoring system (referred to as the subacromial impingement syndrome score, SAISS) based on a literature review and expert opinion [22][23][24][25][26][27]. Comparable approaches were used to create scoring systems in previous studies [11,28,29].…”
Section: Evaluation Of Educational Qualitymentioning
confidence: 99%
“…However, the strength of evidence supporting this recommendation is limited and findings from two large trials found exercise therapy did not provide additional benefit over usual care 9 10. On the other hand, a recent systematic review and network meta-analysis suggested that, among other interventions, exercise and manual therapy are likely to be effective in the short term for pain and function outcomes 11. Currently, it is uncertain: (1) if exercise therapy is more effective than placebo; (2) which form of exercise therapy is likely to be more effective; (3) whether exercise combined with manual therapy is likely to be more effective than exercise alone.…”
Section: Introductionmentioning
confidence: 99%
“…The role of manual therapy in the management of patients with shoulder subacromial pain is unclear and debated in the literature 17. There are conflicting recommendations from previous trials and reviews in the topic 11 14 17 18. Evidence from trials on other musculoskeletal disorders suggests that including manual therapy led to better clinical outcomes when compared with corticosteroid injection or wait-and-see in the management of other musculoskeletal disorders (eg, tennis elbow),19 or usual care when managing patients with hip or knee osteoarthritis 20.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations